Coaching Student Learning in Providing Authentic Assessment and Effectiveness of Distance Learning - Tri Aspiyana; Desak Ketut Angraeni; I Komang Mertayasa (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2021)
The problems that exist in the new learning system are the main focus in solving educational problems on a national scale. The problems that arise are regarding the learning support facilities experienced by students in carrying out distance learning and limited face-to-face learning. This problem allows student assessment to be non-objective in the learning process, so that it will affect the achievement of the learning objectives that have been set. One aspect of good education services is to provide the best possible facilities to students, both in terms of individual, social, aspirations, needs and potentials. For this reason, student management is needed to be able to provide convenience in facilitating it. One of them is through coaching and developing students so that the student learning experience can be carried out optimally and effectively.